Charge movements near the mechanical threshold in skeletal muscle of Rana temporaria. - Adrian, R H (1984)
Charge movement was investigated over a range of potentials close to the mechanical threshold in voltage-clamped frog skeletal muscle. The delayed (q gamma) component of the charging currents appeared with a time course lasting well over 100 ms at around -50 to -40 mV, but the currents became larger and faster with further depolarization. The slow charging current was investigated using a 10 mV probe step intercepting the time course of these currents. This procedure showed that the charging currents could last as long as 100-300 ms. The total charge was conserved when the charging current was small and prolonged. The results can be related directly to earlier findings concerning contractile activation of muscle by applied voltage steps to potentials near threshold ( Adrian , Chandler & Hodgkin, 1969).